Analisis Skeptivitas Gubernur DKI Jakarta terhadap Kesahihan Laporan Audit BPK RI Ditinjau dari Standar Pemeriksaan Akuntan - Yulifati Laoli (Pusat P2M Politeknik Negeri Batam, 2017)
The general objective of this study is to provide an extra input, so that the accuracy of the BPK audit report indisputable future and the results can be trusted by the public, both in terms of standard of examination and in terms of the law. The specific objectives of this study was to straighten out the friction that occurs between the Governor of Jakarta to the BPK, on matters of state losses amounting Rp191.897455.000,00 on purchases of land by the provincial government. DKI-Jakarta from RSU-Sources Sane. The method used in this study is a research method documentation - comparative. The analytical method used to process data analysis is descriptive-explanatory. These results indicate that the BPK-RI opinion can be considered valid for the inspection procedure has been carried out in accordance SPKN. But on the other hand rebuttal Governor of DKI Jakarta, also can not be considered wrong because there is no loss to the state-owned land on RSU The purchase transaction-Sources Sane and the transaction is legitimate, because it was in accordance with contract law as stipulated in the Civil Code.